LncRNA MDRL Mitigates Atherosclerosis through miR-361/SQSTM1/NLRP3 Signaling - Ling You; Yanjie Zheng; Jing Yang; Qian Hou; Lianxia Wang; Yan Zhang; Chunxia Zhao; Ruiqin Xie (Mediators of Inflammation)
Objective. Long non-coding RNAs (lncRNAs) play many important roles in gene regulation and disease pathogenesis. Here, we sought to determine that mitochondrial dynamic related lncRNA (MDRL) modulates NLRP3 inflammasome activation and apoptosis of vascular smooth muscle cells (VSMCs) and protects arteries against atherosclerosis. Methods. In vivo experiments, we applied LDLR knockout (LDLR-/-) mice fed the high-fat diet to investigate the effects of MDRL on atherosclerosis. In vitro experiments, we applied mouse aortic smooth muscle cells to determine the mechanism of MDRL in abrogating NLRP3 inflammasome and inhibiting cell apoptosis through miR-361/sequentosome 1 (SQSTM1) by TUNEL staining, quantitative RT-PCR, western blot, microribonucleoprotein immunoprecipitation, and luciferase reporter assay. Results. Downregulated MDRL and increased NLRP3 were observed in mouse atherosclerotic plaques, accompanied with the increase of miR-361. The results showed that MDRL overexpression significantly attenuated the burden of atherosclerotic plaque and facilitated plaque stability through inhibiting NLRP3 inflammasome activation and cell apoptosis, and vice versa. Mechanically, MDRL suppressed NLRP3 inflammasome activation and VSMC apoptosis via suppressing miR-361. Furthermore, miR-361 directly bound to the 3’UTR of SQSTM1 and inhibited its translation, subsequently activating NLRP3 inflammasome. Systematic delivery of miR-361 partly counteracted the beneficial effects of MDRL overexpression on atherosclerotic development in LDLR-/- mice. Conclusions. In summary, MDRL alleviates NLRP3 inflammasome activation and apoptosis in VSMCs through miR-361/SQSTM1/NLRP3 pathway during atherogenesis. These data indicate that MDRL and inhibition of miR-361 represent potential therapeutic targets in atherosclerosis-related diseases.